Una versión toscana del Contrasto dell’anima con lo corpo de Antonio di Oliveri - NÚÑEZ ROMÁN , Francisco (Cuadernos de Filología Italiana, 2010)
In this paper we edit for the first time a Tuscan version of the Contrasto dell’anima con lo corpo of the Sicilian author Antonio de Oliveri, preserved in the Biblioteca Capitular Colombina of Seville. After a short introduction about the literary debates in the Middle Age, we pay special attention to the debates between the soul and the body and then we analyze the differences found in the Tuscan and the Sicilian versions, trying to suggest also an hypothesis about the responsibility of the Tuscan version and the no completeness of the Sicilian one. Finally, we present the full edition of the text.